Uji Antibakteri secara Klinis Ekstrak Kulit Manggis (Garcinia mangostana L.) dalam Saluran Akar Gigi Tikus (Rattus norvegicus) Clinically Antibacterial Test of Pod Mangosteen (Garcinia mangostana L.) in Dental Root Canal Rat (Rattus norvegicus) - Farah Firdha Abadhia; Sri Lestari; Dyah Setyorini (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Background. Root canal irrigation is important for debridement and disinfection in rootcanal treatment to eliminate population of microorganisms that exist in the root canal.Irrigation materials must be biocompatible and can not cause biological response.Objective. The aim of this study was to determine the effect of pod Mangosteen extractas alternative root canal irrigation materials to eliminate bacterial colonies. Method. Thisresearch was experimental study with post test control group design. The method wasdone by counting the number of mix bacterial colonies in the media used colony countertool. 24 samples were divided into 4 groups, they were 80% pod mangosteen extract,100% pod mangosteen extract, 2.5% NaOCl and distilled water. Results andConclusions. Pod mangosteen extract with 100% concentration had antibacterialcapabilities similar to 2.5% NaOCl. Pod mangosteen extract (Garcinia mangostana L.)was able to eliminate mix bacteria in root canals.Keywords: biocompatible, irrigation materials, the mangosteen peel extract, the numberof mix bacterial colonies